The Legacy of Christopher Columbus in the Americas : New Nations and a Transatlantic Discourse of Empire - Bartosik-Velez, Elise, 1966- (Book collections on Project MUSE., 2014)
"Explains the popularity of Christopher Columbus in the early Americas. Illustrates how New World representations of Columbus integrate older discourses of empire. Shows how the idea of empire was significant in the construction of the new nations of the Americas"--Provided by publisher